Acceleration Of Msmes (Micro, Small And Medium Enterprises) In The Role Of Expanding Economic Growth In Indonesia - Anggia Ramadhan; Lic.Rer.Reg. Sirojuzilam; M. Syafii (Jurnal Ekonomi, 2024)
MSMEs (Micro, Small, and Medium Enterprises) play a strategic role in supporting Indonesia's economic growth, both through their contribution to GDP, employment absorption, and expansion of domestic and international markets. This study aims to analyze the acceleration of MSMEs in the expansion of national economic growth, with a focus on key factors that influence the ability of MSMEs to grow, innovate, and compete in the global market. This research approach uses a mixed method, involving quantitative analysis of secondary data from the Central Statistics Agency (BPS) and the Ministry of Cooperatives and MSMEs, as well as in-depth interviews with MSME actors in various sectors. The results of the study show that MSME acceleration is influenced by three main factors: business digitalization, access to financing, and improving human resource skills. The implementation of digital technology has been proven to increase operational efficiency and expand market access, both locally and internationally. However, obstacles such as low digital literacy, limited capital, and suboptimal regulations are still major challenges. This study recommends strengthening policies that support MSME digitalization, providing inclusive access to financing, and more focused entrepreneurship training and education. With targeted acceleration, MSMEs have great potential to become the main driving force of Indonesia's sustainable and inclusive economic growth.